2020
DOI: 10.1002/ppul.25160
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and quality of life in adolescents with asthma and fixed airflow obstruction

Abstract: Asthma is a disease characterized by reversible bronchoconstriction, but some subjects develop fixed airflow obstruction (FAO). Subjects with FAO present more asthma symptoms and may have increased sedentary behavior; however, the effect of FAO on aerobic fitness and physical activity levels (PAL) remains poorly understood. Aim To compare adolescents with asthma and FAO and adolescents with asthma without FAO in terms of aerobic fitness, PAL, muscle strength, and health‐related quality of life (HRQoL). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
6
0
3
Order By: Relevance
“…The components of physical fitness are approached both from the perspective of health, including five parameters (cardiovascular/aerobics fitness, strength, muscular endurance, flexibility, body composition), and physical activities, including additional six parameters (agility, balance, coordination, speed, reaction time, power) [34][35][36]. Both perspectives have been addressed in numerous studies, which have highlighted the importance of developing fitness since childhood in order to form proactive behaviors with a major impact on physical development, health, social integration and quality of life [36][37][38][39][40] among adulthood. Moreover, fitness and physical activity are important for cardiovascular and mental health, but activity and fitness levels are declining especially in adolescents and among girls [37].…”
Section: Introductionmentioning
confidence: 99%
“…The components of physical fitness are approached both from the perspective of health, including five parameters (cardiovascular/aerobics fitness, strength, muscular endurance, flexibility, body composition), and physical activities, including additional six parameters (agility, balance, coordination, speed, reaction time, power) [34][35][36]. Both perspectives have been addressed in numerous studies, which have highlighted the importance of developing fitness since childhood in order to form proactive behaviors with a major impact on physical development, health, social integration and quality of life [36][37][38][39][40] among adulthood. Moreover, fitness and physical activity are important for cardiovascular and mental health, but activity and fitness levels are declining especially in adolescents and among girls [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, RD problems in adolescence are not only highly likely to continue into adulthood, but also have adverse impacts on quality of life, disability, and productivity [ 40 ]. Despite many studies that have emphasized the importance of maintaining appropriate PA and fitness to ameliorate RD [ 41 , 42 ], the current evidence on HRPF in adolescents with RD is ambiguous, and some studies have even demonstrated the outcomes measured by only a specific HRPF of adolescents with RD [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Застосування кластерного аналізу дало змогу виділити різноманітні фенотипи БА з урахуванням віку початку захворювання, характеру тригерних стимулів, особливості від повіді на лікування, характеру й активності запалення бронхів і результатів функціональ них тестів легень [16,26]. Отримані дані дають підстави вважати, що БА не зводиться лише до простої концепції хронічного запалення дихальних шляхів, проте є гетерогенним захво рюванням, лікування якого з позицій «один розмір для всіх» є малоефективним [30].…”
Section: ек колоскова оа шахова си тарнавская ев власоваunclassified
“…Ремоделювання бронхів визначає їх гіпер чутливість і, особливо, гіперреактивність у від повідь на інгаляційні стимули. Цей вплив структурних змін бронхів на ГСБ може відбу ватися незалежно від участі клітин у запаленні ДШ за рахунок активації резидентних клітин легень [26]. Тому можна припустити, що в май бутньому перспективним у лікуванні БА буде не лише пошук нових протизапальних препара тів, але й розробка засобів впливу на взаємодію епітелію з підлеглими структурами бронхів.…”
Section: ек колоскова оа шахова си тарнавская ев власоваunclassified
See 1 more Smart Citation